Association of rs16917496 polymorphism at the miR-502 binding site in the SET8 3'UTR with the risk of Prostate Cancer and benign prostatic hyperplasia - Haj Manochehri, Mahsa; Azizi, Faezeh; Rahimi, Mahnoosh; Omrani, Mir Davood (Novelty in Biomedicine, 2018)
Background: MicroRNAs (miRNAs) can bind to the 3'-untranslated regions (UTRs) of messenger RNAs, where they interfere with translation and thereby regulate cell differentiation, apoptosis, and tumorigenesis. Genetic polymorphisms in the 3'-UTRs targeted by miRNAs alter the strength of miRNA binding in a manner that affects the behavior of individual miRNAs. The histone methyltransferase SET8 has been reported to be a regulator of Tumor Protein 53 (TP53) methylation, a tumor suppressor gene, and regulate genomic stability. Furthermore, an association between the TP53 and Prostate Cancer has been reported in several studies. The present study aimed to evaluate whether (rs16917496) polymorphism at the miR-502 binding site in the 3' untranslated region of the histone methyltransferase SET8 is associated with the expression of this gene in Benign Prostatic Hyperplasia (BPH) and prostate cancer (PCa) patients. Materials and Methods: We examined whether an rs16917496 polymorphism is associated with the risk of PCa and BPH in the Iranian population. This case-control study included 40 patients with pathologically confirmed PCa, 59 patients with BPH, and 45 controls. The rs16917496 polymorphism was determined using a restriction fragment length polymorphism (RFLP). Results: We found significant association of rs16917496 in benign prostatic hyperplasia (BPH). The most frequent genotype in the control, prostate cancer, and BPH groups were TT, TC, and CC, respectively. Conclusion: This study demonstrates that the heterozygote genotype of the SET8 polymorphism in the mir-502 gene could be considered a risk factor for the emergence of prostate cancer.